They Say that Heaven is a Free Range - Ton Haak; Antonia Zoutenbier (Symphony in the Flint Hills, 2017)
Introduction: It still feels a little weird, living in this part of the Western hemisphere, where, more than a century after he is commonly said to have disappeared, the cowboy is still very much alive, and the free-ranging beef cattle are kicking too. In this place, life is still based on the outdoors, a few nineteenth-century customs, and the survival of the fittest.
Keywords: cowboy culture; Flint Hills; prairie; ranching; cowboys